The Effect of Students' Learning Independence and Cognitive Learning Style on Atomic Physics PEFI4421 Learning Achievement - *, Prayekti; Rasyid, Rasyimah (IJRDO- Journal of Educational Research, 2017)
In this study, the researcher explored the contributions of independence in learning and cognitivelearning style towards students' learning achievement on Atomic Physics course PEFI4421 insemester 1, 2017 academic year. This study employed a double linear regression analysis. Theanalysis measured influences of a free variable on a bound variable. The measurement of thisinfluence included one free variable (X) and one bound variable (Y), called the simple linearregression analysis with the following formula Y = a+bX. In this study, this formula was usedfor measuring the contribution of two free variables on one bound variable. Sample of this studywere the students that already passed the Atomic Physics course in Open University Indonesiaunder 2016 (2 semesters) and 2017 (1 semester) academic year with an underlying assumptionthat the students were homogenous since they all had completed the course in a considerablyrecent time period. The results of this study showed that (1) not all of the students of PhysicsEducation had the learning materials of Atomic Physics; (2) the students who dominantly had afield independent cognitive learning style and learning independence achieved maximumlearning achievements of Atomic Physics; and (3) the students' graduation year did not determinethe influence of the cognitive learning style and learning independence since their graduationyears were still considered to be recent.